On the nature of the episodic gamma-ray flare observed in Cygnus X-1 - Valle, María Victoria del (2009)
The high-mass microquasar Cygnus X-1, the best established candidate for a stellar-mass black hole, has been detected in a flaring state at very high energies, E > 200 GeV (Albert et al. 2007). The observation was per- formed by the Atmospheric Cherenkov Telescope MAGIC. It is the first experimental evidence of very high energy emission produced by a galactic stellar-mass black hole. The observed high energy excess occurred in coin- cidence with an X-ray flare. The flare took place at orbital phase = 0.91, being = 1 the moment when the black hole is behind the companion star. In this configuration the absorption of gamma-ray photons produced by photon-photon annihilation with the stellar field is expected to be the highest. We present detailed calculations of the gamma-ray opacity due to pair creation along the whole orbit, and for different locations of the emitter (height above the compact object). We discuss the location of the gamma- ray producing region in Cygnus X-1 and the energetics required to produce the flare.